Driving Forces Of The Development Of Suburban Landscape – A Case Study Of The Sulkov Site West Of Pilsen - Kopp, Jan; Frajer, Jindřich; Pavelková, Renata (Quaestiones Geographicae, 2015)
In the study area of the Sulkov site in the western part of the suburban landscape of the city of Pilsen we focus on detailed historical analysis of the development of the landscape, which has undergone significant changes, and thus clearly demonstrates the impact of the driving forces on both the regional and inter-regional levels. The documented historical development of ecotopes proved that the fundamental changes in the use of the natural potential had been determined by social and economical demand. The specific use of each type of ecotopes of the site was then co-decided by the natural potential of the area and the geographic location with good transport connection, i.e. local and regional factors.